2015
DOI: 10.15171/hpp.2015.014
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Diet and Nutrition Education Program among Women of Reproductive Age: a Necessity of Multilevel Strategies or Community Responsibility

Abstract: Article type: Review ArticleBackground: Reproductive years represent a major proportion of women"s life. This review focuses on recommended nutritional considerations, physical activity pattern as well as the effect of nutrition education (NE) on behavior modification and health outcomes of women of reproductive age using either singlelevel, multiple-level or community-level interventions. Methods: For this narrative review, numerous searches were conducted on databases of PubMed, Science Direct and Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 50 publications
2
35
0
1
Order By: Relevance
“…They are also at risk for poor dietary practice and poor behavioral modi cation in terms of eating habit and dietary diversi cation. Even they may not have enough monthly income for good food diversity and [69]. This gure is in line with systematic review done in Africa and studies done in Pakistan and Bangladesh [17,61,66].…”
Section: Discussionsupporting
confidence: 80%
“…They are also at risk for poor dietary practice and poor behavioral modi cation in terms of eating habit and dietary diversi cation. Even they may not have enough monthly income for good food diversity and [69]. This gure is in line with systematic review done in Africa and studies done in Pakistan and Bangladesh [17,61,66].…”
Section: Discussionsupporting
confidence: 80%
“…Integration of these different options based on specific target groups could improve nutritional outcomes. 71,72 Surveillance and immunization studies were limited but significantly effective where implemented. Thus, previous reviews have highlighted the importance of research in both areas in humanitarian settings.…”
Section: Health Intervention Effectivenessmentioning
confidence: 99%
“…Such differences could have many implications in designing nutrition intervention programs among others. For instance, it has been suggested that nutrition interventions are more successful when women are the target as they influence household diets (Dunneram & Jeewon, ; IFPRI, ; Robinson, ). However, according to this study, familiarity greatly influences food choices of Malawian women compared to men.…”
Section: Discussionmentioning
confidence: 99%